THE ACTIVITY OF NATIVE HONEY AGAINST SOME MICROORGANISMS - Waleed, Sinai (Iraqi Journal of Science, 2024)
The present study was conducted to detect the susceptibility of six microorganisms isolated from patients suffering from urinary tract and wound infections against native honey, by the agar-well diffusion method. These isolates included: Pseudomonas sp., Klebseiila sp., Escherichia coli, Proteus sp., Staphylococcus aureus and Candida albicans. The results showed that the bacteria isolates were resistant against most of the antibiotics uesd. Two isolates were sensitive to Amikacin and Co- trimoxazole, while all isolates were resistant to Gintamycin and Cephotaxime. In contrast, honey at 5% concentration was able to inhibit the growth of most microorganisms tested, with the exception of only Pseudomonas sp., which was inhibited at concentration